Inovasi Teknologi Pencacahan Tanaman Dengan Pemodelan Pisau untuk Mendukung Kompos Berbasis Biopori pada Lingkungan Berkelanjutan - Yasin, Azalia Fajri; Irnawati, Irnawati; Riskawati, Riskawati; Ekananda, Bintang; Rahmatullah, Azwar (Jurnal Teknologi Lingkungan Lahan Basah, 2026)
Organic waste management is a strategic effort in promoting sustainable agriculture and environmental preservation. This article aims to design a plant shredding machine to accelerate the decomposition of organic materials, particularly within biopore systems. The research method includes identifying functional requirements, mechanical design, selecting materials and components, and conducting work simulation and performance testing. The materials used in testing consist of dry leaves, small twigs, and household plant waste. The design results indicate that the shredding machine can produce chopped material that accelerates composting and facilitates biopore filling. The machine is also considered energy-efficient and environmentally friendly, making it potentially applicable at the household and community levels. This innovation is expected to enhance public participation in independent organic waste processing.